Ocena poziomu wiedzy studentów wybranych polskich uczelni wyższych na temat zasad udzielania pierwszej pomocy osobie dorosłej w stanach nagłych = Assessment of knowledge about delivering first aid for an adult in emergency situations among students from selected Polish universities - Rafał Czyż; Marta Kwiatoń; Izabela Górniak (Kazimierz Wielki University, 2016)
Czyż Rafał, Kwiatoń Marta, Górniak Izabela. Ocena poziomu wiedzy studentów wybranych polskich uczelni wyższych na temat zasad udzielania pierwszej pomocy osobie dorosłej w stanach nagłych = Assessment of knowledge about delivering first aid for an adult in emergency situations among students from selected Polish universities. Journal of Education, Health and Sport. 2016;6(7):399-410. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58327 http://ojs.ukw.edu.pl/index.php/johs/article/view/3704       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 15.07.2016.     Ocena poziomu wiedzy studentów wybranych polskich uczelni wyższych na temat zasad udzielania pierwszej pomocy osobie dorosłej w stanach nagłych   Rafał Czyż1 (rafalczyz1990@o2.pl), Marta Kwiatoń1, Izabela Górniak2   1) Katedra Medycyny Ratunkowej Uniwersytetu Medycznego im. Piastów Śląskich we Wrocławiu 2) Uniwersytet Medyczny im. Piastów Śląskich we Wrocławiu   Udzielanie pierwszej pomocy na miejscu zdarzenia stanowi istotne ogniwo łańcucha przeżycia. Młodą i aktywną, a przede wszystkim bardzo liczną grupą społeczną są studenci, dlatego tak ważne jest, aby aktualne wytyczne udzielania pierwszej pomocy były im dobrze znane. Celem niniejszego badania była ocena poziomu wiedzy studentów z zakresu udzielania pierwszej pomocy w sytuacjach nagłych. Anonimowa i autorska ankieta została rozdystrybuowana wśród 459 studentów z Wrocławia, Poznania i Bydgoszczy (59% kobiet, 41% mężczyzn) w wieku 22,5 ± 1,9 lat. Kwestionariusz zawierał 19 pytań, w tym test wiedzy z zakresu pierwszej pomocy o maksymalnej do zdobycia ilości punktów: 7. Średni wynik testu wiedzy z zakresu pierwszej pomocy w ogólnej grupie badanej wyniósł 4,7 ± 1,2 punktów. Najwyższy średni wynik uzyskali studenci z Wrocławia,  najniższy natomiast - studenci z Poznania (5,0 ± 1,3 vs. 4,2 ± 1,1). Grupa studentów z Bydgoszczy uzyskała średni wynik na poziomie 4,6 ± 1,1. Zaledwie 14% studentów zdeklarowało, że brało udział w zajęciach pierwszej pomocy organizowanych przez uczelnię. Alarmujący wydaje się również fakt, iż około 30% studentów nigdy nie uczestniczyło w żadnym szkoleniu, podczas gdy ponad 32% badanych znalazło się w przeszłości w sytuacji, w której musieli udzielić pierwszej pomocy osobie poszkodowanej. Z kolei o automatycznym defibrylatorze zewnętrznym słyszało ponad 84% uczniów, jednakże jedynie 76% z nich wie dokładnie, co to za urządzenie i do czego służy. Ponad 96% studentów jest świadomych o prawnym zobowiązaniu do udzielania pierwszej pomocy osobie poszkodowanej. Wiedza studentów na temat udzielania pierwszej pomocy jest niewystarczająca. Istnieje potrzeba organizacji kursów przypominających z zakresu udzielania pomocy oraz najnowszych algorytmów pierwszej pomocy.   Słowa kluczowe: pierwsza pomoc, studenci, stany nagłe.     Assessment of knowledge about delivering first aid for an adult in emergency situations among students from selected Polish universities     Delivering first aid at the spot of the accident is an essential link of the survival chain. A young and active socially group like students should know current first aid guidelines. The aim of this study was to evaluate the level of students' knowledge in delivering first aid in emergency situations. Anonymous and author's survey was carried out on a group of 459 students from Wrocław, Poznań and Bydgoszcz (59% women, 41% men) aged 22.5 ± 1.9. The questionnaire comprised of 19 questions about general experience with first aid and quiz questions about practical knowledge in first aid delivery. The maximal amount of points to obtain in the quiz was 7.             The average result for the quiz section of the questionnaire for the entire examined group amounted to 4.7 ± 1.2 points. The highest average result got students from Wrocław and the lowest average result got students from Poznań (5.0 ± 1.3 vs. 4.2 ± 1.1). Student group from Bydgoszcz achieved the average result of 4.6 ± 1.1 points. Only 14% of students declared participation in lessons about delivering first aid organized by the college. Also alarming seems the fact that about 30% of the students never took part in such training. Over the 32% of the examined students was in an emergency situation that required them to provide first help to an injured person. About the automated external defibrillator heard over the 84% of those surveyed, however, only 76% of them know exactly what it is and what the device is used for. Over the 96% of the students are aware of the material fact of obliging to delivering first aid to an injured person. Students knowledge about delivering first aid is insufficient. There is a need to organize refresher courses about delivering first aid and the newest first aid algorithms.   Key words: first help, students, emergencies.